Association between timing of dialysis initiation and clinical outcomes in the paediatric population: an ESPN/ERA-EDTA registry study. Issue 11 (30th April 2019) - Preka, Evgenia; Bonthuis, Marjolein; Harambat, Jerome; Jager, Kitty J; Groothoff, Jaap W; Baiko, Sergey; Bayazit, Aysun K; Boehm, Michael; Cvetkovic, Mirjana; Edvardsson, Vidar O; Fomina, Svitlana; Heaf, James G; et al.
Abstract: Background: There is no consensus regarding the timing of dialysis therapy initiation for end-stage kidney disease (ESKD) in children. As studies investigating the association between timing of dialysis initiation and clinical outcomes are lacking, we aimed to study this relationship in a cohort of European children who started maintenance dialysis treatment. Methods: We used data on 2963 children from 21 different countries included in the European Society of Pediatric Nephrology/European Renal Association–European Dialysis and Transplant Association Registry who started renal replacement therapy before 18 years of age between 2000 and 2014. We compared two groups according to the estimated glomerular filtration rate (eGFR) at start: eGFR ≥8 mL/min/1.73 m 2 (early starters) and eGFR <8 mL/min/1.73 m 2 (late starters). The primary outcomes were patient survival and access to transplantation. Secondary outcomes were growth and cardiovascular risk factors. Sensitivity analyses were performed to account for selection- and lead time-bias. Results: The median eGFR at the start of dialysis was 6.1 for late versus 10.5 mL/min/1.73 m 2 for early starters. Early starters were older [median: 11.0, interquartile range (IQR): 5.7–14.5 versus 9.4, IQR: 2.6–14.1 years]. There were no differences observed between the two groups in mortality and access to transplantation at 1, 2 and 5 years of follow-up. One-year evolution of height standard deviation scores was similar among the groups, whereas hypertension was more prevalent among late initiators. Sensitivity analyses resulted in similar findings. Conclusions: We found no evidence for a clinically relevant benefit of early start of dialysis in children with ESKD. Presence of cardiovascular risk factors, such as high blood pressure, should be taken into account when deciding to initiate or postpone dialysis in children with ESKD, as this affects the survival.